Clinician-reported barriers to providing perinatal care to women with intellectual and developmental disabilities. Issue 1 (2nd January 2023) - Smith, Lauren D.; Valentine, Anne; Moore Simas, Tiffany A.; Parish, Susan L.; Levy, Alanna; Mitra, Monika
ABSTRACT: Background: Research suggests that women with intellectual and developmental disabilities are at increased risk for adverse pregnancy outcomes. Further, they report unmet perinatal care needs. This qualitative study examined clinician perspectives on barriers to providing perinatal care to women with intellectual and developmental disabilities. Method: We conducted semi-structured interviews and one focus group with US obstetric care clinicians ( n = 17). We used a content analysis approach to code data and analyse them for larger themes and relationships. Results: the majority of participants were white, non-Hispanic, and female. Participants reported barriers providing care to pregnant women with intellectual and developmental disabilities across individual (e.g., communication challenges), practice (e.g., identification of disability status), and system levels (e.g., lack of clinician training). Conclusions: clinician training and evidence-based guidelines for perinatal care of women with intellectual and developmental disabilities as well as services and supports during pregnancy are needed.